Understanding the Spiritual Development of Muslim Children: Educational Implications - Widianingsih Widianingsih (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2024)
This research aims to understand the spiritual development of Muslim children and its implications in the context of formal education and family environment. Spiritual development in children is considered important because it plays a role in shaping character and basic moral values from an early age. This study uses a descriptive quantitative method involving a sample of children aged 6-12 years from three Islamic schools in city X. Data was collected through questionnaires to students, observations in the school environment, and interviews with teachers to better understand aspects of children's spiritual development. The results of the study show that children's spiritual development is greatly influenced by the family environment and formal education. Children from families who are active in worship activities show a deeper understanding of the concept of divinity, higher awareness of worship, and better moral behavior. In addition, religious programs held in schools play a significant role in shaping children's awareness of religious values and improving spiritual reflection skills. This study suggests that the Islamic education curriculum in formal schools continues to integrate spiritual values in a structured manner to support the formation of Muslim children's character with noble character and strong religious understanding. This finding is expected to be the basis for the development of a comprehensive religious education curriculum that is relevant to the needs of children in the modern era